THE INFLUENCE OF GREEN ACCOUNTING ON COMPANY VALUE WITH PROFITABILITY AS A MEDIATING VARIABLE - Yunitasari, Dwi Safira; Kodir, Mokhamad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to determine and analyze the effect of green accounting on firm value, to determine and analyze the effect of green accounting on profitability, to determine and analyze the effect of profitability on firm value, to determine and analyze the effect of green accounting on firm value with profitability as a mediating variable. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period with a population of 233 companies. The sampling technique used was purposive sampling with a total sample of 51 companies used in this study with a total of 204 observations. A panel data regression model was used in this study as a data analysis method. The results showed that green accounting had a positive effect on firm value, green accounting had no positive effect on profitability, profitability had no positive effect on firm value, and profitability was unable to mediate the effect of green accounting on firm value.